2023
DOI: 10.3390/plants12193464
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Supplementation Alleviates the Salinity-Stress-Mediated Growth Decline in Wheat (Triticum aestivum L.) by Modulating Tolerance Mechanisms

Khalid H. Alamer

Abstract: The impact of the exogenous supplementation of hydrogen sulfide (20 and 50 µM HS) on growth, enzyme activity, chlorophyll pigments, and tolerance mechanisms was studied in salinity-stressed (100 mM NaCl) wheat. Salinity significantly reduced height, fresh and dry weight, chlorophyll, and carotenoids. However, the supplementation of HS (at both concentrations) increased these attributes and also mitigated the decline to a considerable extent. The exogenous supplementation of HS reduced the accumulation of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The H 2 S priming alleviated these cellular aberrations of the mesophyll cells by H 2 S role in biomembrane repairing [ 34 ], ROS scavenging, Na + , and Cl − uptake restriction as well as K + and Ca 2+ content elevation [ 35 ], resulting in membrane integrity and osmotic balance maintenance reflected in the elevated value of MSI found in this work. Alamer [ 84 ] also reported a similar alleviating impact on the MSI by H 2 S supply under salinity stress in wheat.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The H 2 S priming alleviated these cellular aberrations of the mesophyll cells by H 2 S role in biomembrane repairing [ 34 ], ROS scavenging, Na + , and Cl − uptake restriction as well as K + and Ca 2+ content elevation [ 35 ], resulting in membrane integrity and osmotic balance maintenance reflected in the elevated value of MSI found in this work. Alamer [ 84 ] also reported a similar alleviating impact on the MSI by H 2 S supply under salinity stress in wheat.…”
Section: Discussionmentioning
confidence: 76%
“…The Rubisco small subunit is indicated to be a potential engineering target to improve the performance of Rubisco [ 19 ], and based on our findings, we recommend it for engineering biology approaches to modulate Rubisco catalysis activating the photosynthesis and hence crop performance under saline conditions. In addition, the accumulation of different osmolytes (soluble sugars, soluble proteins, and carotenoids) in the sunflower seedlings in response to H 2 S priming in the current study, is suggestive of their role in protecting the architecture and functions of the chloroplast membranes, enzymes, and other cell structures against ROS damage and the toxicity of greater concentrations of intracellular toxic ions, as well as acting as osmotic regulators [ 18 , 34 , 81 84 ], which resulted in enhanced photosynthesis, stabilized subcellular structures, and osmotic adjustment, and ultimately the adaptability of sunflower seedlings to NaCl stress. Moreover, NaCl-enhanced burst of proline in sunflower seedlings (more so in roots) might be associated with salinity-induced ABA content observed in this research as ABA has been reported to elevate proline production in various stressed plants under saline conditions [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 76%